The Impact of COVID 19 Towards International Business Strategy: A study of Coca-Cola Company - Nair, Rajesh Kumar; Reddy, L. Sudershan; Verma, Priyanka; Pandey, Rudresh; Yuwono, Sienly; Sin, Liem Gai; Qi, Wong Yun; Kee, Daisy Mui Hung; Gee, Ooi Xin; Ing, Tammy Wong Shao; Yu, Tan Pei (AIBPM Publisher, 2021)
Coca Cola is one of the largest beverage companies in the world and becomes one of the favourite drinks for all people around the world. On March 11, 2020, World Health Organization (WHO) agrees to receive COVID – 19 outbreak a pandemic. This problem firstly started in China; it becomes the main problem of the World. As many Organizations whether domestic and international business affected by this epidemic. International business which is easily affected by the crisis as war, terrorist attacks, natural disasters and another. The main aim of this study is to analysis the global strategy and operations of Coca-Cola Company during COVID–19 pandemic. To collect the data, the questionnaire was distributed to 250 respondents, who are the employees of Coca-Cola company. The questionnaire was distributed via email. The impact of occurrence of Coronavirus on the international business. The results shows that the percentage of respondents who buy Coca-Cola products at online shopping platform increased during the pandemic